The effect of the accounting expertise of chief financial officers on corporate credit ratings. Issue 2 (4th March 2022) - Chen, Ming-Chin; Chang, Chia-Wen
ABSTRACT: Corporate credit ratings (CRs) are closely related to companies' cost of debt financing. Recent research has drawn wide attention to how nonfinancial as well as financial factors may affect ratings. By manually collecting information about the profiles of chief financial officers (CFOs) of US companies, we examine the effect of CFOs' accounting expertise on corporate CRs. The results show that firms with accounting expert CFOs are more likely to receive higher CRs and that the effect of CFOs' accounting expertise on the ratings is more pronounced for firms with higher default risk, suggesting that the accounting expertise of CFOs may be an important factor that affects CRs. Moreover, we find a dynamic relation between accounting expert CFOs and CRs such that a downgrade in a firm's CR in a prior year affects the subsequent selection of an accounting expert CFO.